Short-term momentum effect: a case of Middle East stock markets - Polak, Petr; Ejaz, Abdullah (Business: Theory and Practice, 2015)
The objective of this paper is to find short-term momentum effect in stock markets of the Middle East and to examine whether short-term momentum profits can be explained by risk-based CAPM model. Seven major stock markets from the Middle East were selected. Short-term momentum effect was found in all seven stock markets and CAPM does not adequately explain the short-term momentum profits but momentum portfolio returns are statistically significant. This paper is first attempt to bring major stock markets of the Middle East together and examine them for the short term momentum effect phenomenon. Future research should include more stock markets in order to have a better understanding of Middle Eastern stock markets.